2011
DOI: 10.3390/pharmaceutics3020141
|View full text |Cite
|
Sign up to set email alerts
|

Live Cell in Vitro and in Vivo Imaging Applications: Accelerating Drug Discovery

Abstract: Dynamic regulation of specific molecular processes and cellular phenotypes in live cell systems reveal unique insights into cell fate and drug pharmacology that are not gained from traditional fixed endpoint assays. Recent advances in microscopic imaging platform technology combined with the development of novel optical biosensors and sophisticated image analysis solutions have increased the scope of live cell imaging applications in drug discovery. We highlight recent literature examples where live cell imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 91 publications
(100 reference statements)
0
54
0
1
Order By: Relevance
“…To improve upon the current high attrition rates and latestage failure in drug development, more innovative and informative approaches to candidate drug selection and clinical design are required (44). Failure to translate drug candidates into clinical benefit suggest that conventional early drug discovery strategies and preclinical models are suboptimal and may poorly predict the heterogeneous drug response to effectively guide clinical dosing or combination strategies (45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To improve upon the current high attrition rates and latestage failure in drug development, more innovative and informative approaches to candidate drug selection and clinical design are required (44). Failure to translate drug candidates into clinical benefit suggest that conventional early drug discovery strategies and preclinical models are suboptimal and may poorly predict the heterogeneous drug response to effectively guide clinical dosing or combination strategies (45).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed topologic analysis at cellular and subcellular resolution in live tumor tissue has enabled precise detection and single cell quantification of subtle changes in protein activity over time that cannot faithfully be achieved using standard fixed endpoint approaches applied to in vitro cultured models or ex vivo immunohistochemical analysis (2,44). Using a genetically engineered model of pancreatic cancer that recapitulates the human disease and a novel therapeutic with shown activity in pancreatic cancer, we have quantified the improvement in drug response associated with combination therapy and illustrate the application and advantages of FLIM-FRET in the drug target validation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmaceutical research and development increasingly involves high-content phenotypic screening of compounds examining numerous cellular parameters by live imaging. This approach requires the use of an automated microscope placed within an environmental chamber allowing for high-throughput analysis of molecular and cell dynamics in thousands of cells placed within multi-well plates (a kinetic imaging platform in pharmaceutical jargon) (Carragher et al, 2012;Isherwood et al, 2011). Again, image processing algorithms are crucial in these screens as it would be impossible to analyse so many samples by eye.…”
Section: The Future Of Cinemicroscopymentioning
confidence: 99%
“…[1][2][3] Although several promising studies have suggested using in situ cellular imaging as a tool, 4,5 investigating the interaction between target proteins and drugs using this tool remains difficult due to a lack of resolution and throughput. Hence, a new probe must be introduced for in situ cellular imaging to become a major process in new drug development.…”
Section: Introductionmentioning
confidence: 99%